Examining the Effects of Sustainable Marketing and Green Product Innovation on Customer Loyalty within an Islamic Business Framework: A Study of Avoskin Consumers in Bandar Lampung - Dwi Cahya Ramadhani; Nurlaili; Agus Kurniawan (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study aims to analyze the effect of sustainable marketing and green product innovation on customer loyalty from the perspective of Islamic business, focusing on Avoskin consumers in Bandar Lampung. In an era of increasing environmental awareness, companies are required to implement sustainable marketing strategies and provide eco-friendly product innovations in accordance with Islamic business ethics. This research uses a quantitative approach by distributing questionnaires to 96 Avoskin consumers in Bandar Lampung. Data analysis was conducted using Partial Least Squares (PLS) to examine the relationships between variables. The results indicate that sustainable marketing and green product innovation have a significant positive effect on customer loyalty. These findings highlight the importance of applying Islamic business principles that prioritize sustainability and environmentally friendly innovation to build long-term relationships with consumers. This study is expected to serve as a reference for cosmetic companies in developing business strategies that are not only profitable but also socially and environmentally responsible.